Evolution of wet muck inflow risk management at El Teniente: lessons learned and current practices - Basaure-Matsumoto, K; Latorre, A; Miranda, P (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
The management of wet muck inflows at El Teniente underground operations has evolved significantly over the past three decades. This paper provides a historical review of risk management practices, consolidating lessons learned from wet muck inflow events and operational strategies for hazard mitigation. The analysis is organised in three parts: an initial stage dominated by reactive actions following fatal accidents and large-scale inflow events; a second stage characterised by preventive closures; and a third stage focused on tele-operation, predictive models to estimate high-risk zones and guidelines for safe production. The main aspects addressed include the development of risk classification frameworks, the introduction of predictive models to identify high-risk conditions, operational trials that supported the development of production guidelines and, finally, the current production management system used to mitigate personnel exposure. Today these practices are an integral part of El Teniente’s underground production system. They enable the recovery of previously restricted sectors and contribute in a sustained manner to the mine’s overall output.
Keywords: wet muck